FORMULATION OPTIMIZATION OF EDAMAME PASTE AND MORINGA LEAF INCORPORATION IN MODIFIED CASSAVA FLOUR NOODLES - Santi Dwi Astuti; Laksmi Putri Ayuningtyas; Condro Wibowo; Ghanafalhan Ridhya Firdaus (Jurnal Gizi dan Pangan Soedirman, 2026)
Noodles are commonly made from wheat flour, while Indonesia still relies heavily on imported wheat. Modified cassava flour (mocaf) has potential as an alternative to wheat flour; however, mocaf-based noodle products still require improvement in their sensory and physicochemical quality. This study aimed to determine the optimum proportion of edamame paste and moringa leaves to improve the sensory and physicochemical properties of dried mocaf noodles. Optimization was performed using response surface methodology with a Central Composite Design with edamame paste (0–30%) and moringa leaves (0–10%) as factors, generating 14 experimental runs. Target responses included green and brown color intensity, cassava, beany, and green flavors within acceptable ranges; maximum elasticity, chewiness, elongation, and overall acceptability; and minimum rehydration time and cooking loss. Most responses were well fitted by quadratic models with satisfactory determination coefficients (R² = 0.59–0.97). The optimum formulation was obtained at 17.53% edamame paste and 1.46% moringa leaves. Increasing edamame paste enhanced green and brown color intensity, beany flavor, elasticity, rehydration time, and elongation but reduced cassava flavor and chewiness. Increasing moringa leaves enhanced green color intensity and green flavor but decreased brown color intensity and overall acceptability. The optimum noodles met the defined sensory and physicochemical criteria.